2014
DOI: 10.3928/1081597x-20140212-02
|View full text |Cite
|
Sign up to set email alerts
|

Air Puff Induced Corneal Vibrations: Theoretical Simulations and Clinical Observations

Abstract: PURPOSE: To investigate air puff induced corneal vibrations and their relationship to the intraocular pressure (IOP), viscoelasticity, mass, and elasticity of the cornea based on theoretical simulations and preliminary clinical observations. METHODS:To simulate the corneal movement during air puff deformation, a kinematic viscoelastic corneal model was developed involving the factors of corneal mass, damping coefficient, elasticity, and IOP. Different parameter values were taken to investigate how factors woul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
61
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 63 publications
(61 citation statements)
references
References 34 publications
(29 reference statements)
0
61
0
Order By: Relevance
“…Corneal air puff tests, which examine the intraocular pressure via an air jet applied on the eye (Han et al 2014), also include a similar configuration of an external pressure applied on an elastic shell laying over a liquid film. Hosoi & Mahadevan (2004) studied the peeling and busting dynamics of a viscous liquid contained between a rigid surface and an elastic sheet.…”
Section: Introductionmentioning
confidence: 99%
“…Corneal air puff tests, which examine the intraocular pressure via an air jet applied on the eye (Han et al 2014), also include a similar configuration of an external pressure applied on an elastic shell laying over a liquid film. Hosoi & Mahadevan (2004) studied the peeling and busting dynamics of a viscous liquid contained between a rigid surface and an elastic sheet.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 For example, keratoconus can pathologically decrease the stiffness of the cornea, leading to a loss in the quality of vision.…”
Section: Introductionmentioning
confidence: 99%
“…1 Hence, assessing corneal biomechanical properties are required for detecting the onset and monitoring progression of the ocular diseases as well as assessing the effects of therapeutic interventions. Previous studies have shown the feasibility of commercially available instruments such as the ocular response analyzer and the CorVis, 2 and emerging techniques such as Brillouin microscopy 3 for estimating corneal biomechanical properties. Although these methods can provide important measurements that can reflect some corneal biomechanical features, quantitative assessment of the corneal viscoelasticity is still a challenge.…”
mentioning
confidence: 99%